2020
DOI: 10.35241/emeraldopenres.13684.2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic, psychological response to quarantine, and knowledge of the disease among inmates in a Nigerian custodial center

Abstract: This was a cross-sectional study to assess the psychological response to quarantine during COVID-19 pandemic and knowledge level about the disease among inmates of a Custodial Center in Enugu, Nigeria. A total of 66 new prison inmates were assessed for psychological distress using the Kessler Psychological Distress Scale (K10); and inmates’ knowledge about COVID-19 using a COVID-19 Knowledge Questionnaire developed by the researchers. Participants had a mean age of 28.39±8.71 years; 63 (95.5%) were male inmate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Okoro et al (2020) observed that inmates of a custodian centre in Enugu state, Nigeria, that attained higher level of education were more knowledgeable about COVID-19 than other inmates. The positive correlation between the scores of COVID-19 knowledge and education level of the respondents perhaps reflects their source of information on the disease and how they understood the information.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Okoro et al (2020) observed that inmates of a custodian centre in Enugu state, Nigeria, that attained higher level of education were more knowledgeable about COVID-19 than other inmates. The positive correlation between the scores of COVID-19 knowledge and education level of the respondents perhaps reflects their source of information on the disease and how they understood the information.…”
Section: Discussionmentioning
confidence: 96%
“…Since the positive response rate to the question (Q6) increased with increasing level of education ( Supplementary Table 1) like the average knowledge score (Table 3), enlightenment programmes on asymptomatic transmission should be included in local health promotional campaigns, targeting especially those with lower levels of education. Okoro et al (2020) observed that inmates of a custodian centre in Enugu state, Nigeria, that attained higher level of education were more knowledgeable about COVID-19 than other inmates. The positive correlation between the scores of COVID-19 knowledge and education level of the respondents perhaps reflects their source of information on the disease and how they understood the information.…”
Section: Sources Of Informationmentioning
confidence: 96%
“…Since the positive response rate to the question (Q6) increased with increasing level of education (Supplementary Table 1) like the average knowledge score (Table 2), enlightenment programmes on asymptomatic transmission should be included in local health promotional campaigns, targeting especially those with lower levels of education. Okoro et al (2020) observed that inmates of a custodian centre in Enugu state, Nigeria that attained higher level of education were more knowledgeable about COVID-19 than other inmates. The positive correlation between the scores of COVID-19 knowledge and education level of the respondents perhaps reflects their source of information on the disease and how they understood the information.…”
Section: Discussionmentioning
confidence: 97%
“…29 Limited disease knowledge may aggravate psychological distress and emotional responses. 30 Therefore, coping styles and disease awareness play a significant role in handling the psychological stress associated with the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%